Answer :

Answer:

[tex]x = - 2 \\ y = - 4[/tex]

Step-by-step explanation:

[tex] - 2x + 2y = - 4 \: \: \: \: \: \\ i.e. \: \: \: - x + y = - 2 \: \: \: \: \: \: \: ...(1)\\ \\ 3x + 3y = - 18 \\ i.e. \: \: \: \: \: \: x + y = - 6\: \: \: \: \: \: \: ...(2)[/tex]

From (1) we get

[tex] x = 2 + y[/tex]

Now put x = 2 + y in equation (2)

[tex]2 + y + y = - 6 \\ 2 + 2y = - 6 \\ 2y = - 6 - 2 \\ 2y = - 8 \\ \\ y = - \frac{8}{2} \\ \\ y = - 4[/tex]

now put y = -4 in equation (1) we get

[tex] - x + ( - 4) = - 2 \\ - x - 4 = - 2 \\ x + 4 = 2 \\ x = 2 - 4 \\ x = - 2[/tex]

Other Questions